Capital Gains Tax Overhang and Price Pressure - JIN, LI (Journal of Finance, 2006)
ABSTRACT I study whether the capital gains tax is an impediment to selling by some investors and if so, to what degree associated delayed selling affects stock prices. I find that selling decisions by institutions serving tax‐sensitive clients are sensitive to cumulative capital gains, a pattern not observed for institutions with predominantly tax‐exempt clients. Moreover, tax‐related underselling impacts stock prices during large earnings surprises for stocks held primarily by tax‐sensitive investors. The corresponding price reactions are less negative (more positive) with higher cumulative capital gains. This price pressure pattern is more severe when arbitrage is more costly.